Metode Reward dan Punishment Untuk Mengoptimalkan Sikap Disiplin Anak Usia Dini di TK Harapan Kita Condong Gading Probolinggo - Putri Loviana Aura Tahlia; Ivonne hafidlatil kiromi (Zuriah Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to improve learning discipline in early childhood at HARAPAN KITA Kindergarten, Condong Gading District, Probolinggo Regency, which includes the way teachers prepare lessons, carry out learning, assess learning, teacher difficulties in learning, and efforts to overcome these difficulties. Discipline is one way to help children develop self-control. Discipline can allow children to have limits to correct their wrong behavior. How to apply child discipline can start at the age of 2-6 through simple things that children do in everyday life such as tidying up toys, washing hands, praying, accepting consequences if they make mistakes, and being responsible with their belongings and taking care of their belongings. others. The attitude of discipline in children aims for children to grow into individuals of high quality, character and skills as role models for society, especially modern society. The application of the Reward and Punishment method is a powerful way to optimize children's discipline. The purpose of this article is to conceptually describe the application of the reward and punishment method to children to optimize discipline